The variation characteristics of fecal microbiota in remission UC patients with anxiety and depression - Xu, Lingyun; Li, Yingchao; He, Yingli (Frontiers in Microbiology, 2023)
Background: UC patients with relapsed disease are most likely to suffer from anxiety and depression. Increasing data indicate that psychological issues can change the composition of intestinal flora. Thus, we aim to seek the variation of intestinal microbiota composition in remission UC patients with anxiety and depression in Northwest China.Results: In this study, 45 UC patients in remission were enrolled. The incidence of anxiety was 33.3%, and the prevalence of depression was 22.2%. There was no statistical difference in the Alpha diversity of fecal microbiota, while Beta diversity had a significant difference between the anxiety group and the non-anxiety group, the depression group and the nondepression group. Species composition analysis results showed, the ratio of Bifidobacterium and Lactobacilales significantly decreased. At the same time, the proportion of the Escherichia-Shigella and Proteus_mirabilis increased in the anxiety groups, the ratio of Faecalibacterium and Bifidobacterium significantly decreased. In contrast, Escherichia-Shigella increased in the depression group at the levels of Genes.Conclusions: It still exists anxiety and depression in UC patients even in the remission period.We first identify that the proportion of probiotics decreases while the pathogens increase in UC patients with anxiety and depression. These findings may provide a new pathophysiological mechanism for recurrence of disease causing by impaired psychological function and a new method for the treatment strategy of UC patients with psychological issues.